Mid-term results after treatment of intertrochanteric femoral fractures with percutaneous compression plate (PCCP). Issue 2 (February 2015) - Shen, Jie; Luo, Fei; Sun, Dong; Huang, Qiang; Xu, Jianzhong; Dong, Shiwu; Xie, Zhao
Abstract Background With the ageing of the population, intertrochanteric femoral fracture is associated with increased morbidity. There is continuing controversy over the best treatment for the injury, and the choice of internal fixation method has been a focus of dispute. The purpose of this study was to evaluate the results of these fractures being treated with the percutaneous compression plate (PCCP) technique. Methods From March 2009 to May 2012, 154 patients with intertrochanteric femoral fractures were treated using the PCCP method. Forty-one patients were excluded from the study. According to the AO classification, the remaining 113 fractures were classified as 35 cases of 31A1 fractures, 59 cases of 31A2 fractures, and 19 cases of 31A3 fractures. The clinical data and imaging results were retrospectively analysed. Results The mean operation time was 42.0 (range, 25–82) min, the mean intraoperative blood loss was 40.5 (range, 10–100) ml, and the mean hospital stay was 8.6 (range, 3–18) days. One patient died of renal failure in the perioperative period. Twelve patients died during the 12 months after surgery. The remaining 100 patients were followed-up for 12–36 months and healed their fractures except one, whose neck screw cut out from the femoral neck after 1 postoperative month and resulting in a revision to a hemiarthroplasty. The mean time to bone healing was 12.6 (range, 6–23) weeks. Sixteen patients had pain. There were 13 major device-related complications, including 5 cases of coxa vara, 4 cases of fracture collapse, 2 cases of head penetration, and 2 cases of fracture collapse combined with head penetration. At the time of the last follow-up, 81 patients had regained a pre-injury level of function. The median Harris hip score was 89 points. The median Parker-Palmer score was 7 points. Patients with poor quality of reduction and bad positioning of neck screw were more likely to suffer complications (p < 0.05). Conclusion The results suggest that the PCCP is an effective and safe method in the treatment of all types of intertrochanteric femoral fractures, but good fracture reduction and ideal positioning of the neck screw are prerequisites for the success of the device.